(untitled) (Світ фінансів, 2017)
Лютий І. О. Алексєєнко Л. М. Стратегічні перспективи ринку фінансового капіталу в контексті інтеграційних процесів. Розкрито етапи становлення європейського фінансового ринку у контексті еволюції інтеграційних процесів у рамках ЄС. Висвітлено проблеми входження України до європейського політичного, економічного, безпекового та правового простору. Аргументовано, що співпраця України з ЄС є важливою умовою її інтеграції у світову економіку, одним із факторів успіху демократичних перетворень. Розглянуто перспективи входження України до ЄЕП. Висвітлено позитивні тенденції та окреслено стратегічні перспективи ринку фінансового капіталу у контексті інтеграційних процесів. Lyutyi I. O., Alekseyenko L. M. Strategy perspectives of financing capital market in the context of integrations processes. Stages of becoming of the European financial market in a context of evolution of integration processes are opened within the framework of EU. Problems of occurrence of Ukraine in the European political, economic, safe and legal space are described. It is argued, that co-operation of Ukraine with EU is the important condition of its integration into economic, one of factors of success of democratic transformations. Prospects of occurrence of Ukraine to UES (Unique economic space) are considered. Positive tendencies are showed and perspectives of market of financial capital in context of integrative processes it is underlined.